Extractive Text Summarization Using Generalized Additive Models with Interactions for Sentence Selection - Camargo da Silva, Vinícius [UNESP]; Paulo Papa, João [UNESP]; Augusto Pontara da Costa, Kelton [UNESP] (INSTICC, 2023)
Automatic Text Summarization (ATS) is becoming relevant with the growth of textual data; however, with the popularization of public large-scale datasets, some recent machine learning approaches have focused on dense models and architectures that, despite producing notable results, usually turn out in models difficult to interpret. Given the challenge behind interpretable learning-based text summarization and the importance it may have for evolving the current state of the ATS field, this work studies the application of two modern Generalized Additive Models with interactions, namely Explainable Boosting Machine and GAMI-Net, to the extractive summarization problem based on linguistic features and binary classification.
Keywords: Interpretable Learning; NLP; Text Summarization